ILLOCUTIONARY ACTS IN THE LANGUAGE OF SELECTED FOOTBALL GOAL COMMENTARIES BY PETER DRURY - Maulani Saskiya; Dedi Sulaeman; Fourus Huznatul Abqoriyyah (Universitas PGRI Palembang, 2026)
Football commentary represents a distinctive form of language that combines factual reporting with emotional expression to enhance audience engagement during sporting events. As one of the most prominent football commentators, Peter Drury is widely recognized for his expressive and impactful language, particularly in goal commentaries. Although previous studies have investigated speech acts in football commentary and the use of figurative language in Peter Drury’s narration, limited attention has been given to the analysis of illocutionary acts in the language of football goal commentaries and their communicative functions. Therefore, this study aims to identify the types of illocutionary acts employed in the language of selected football goal commentaries by Peter Drury and to examine the communicative functions reflected in their distribution. Using a descriptive qualitative approach, this study analyzed 113 utterances taken from 32 goal commentary segments compiled in a YouTube video, based on Searle’s taxonomy of illocutionary acts. The findings revealed three categories of illocutionary acts: expressive (75.22%), assertive (23.89%), and directive (0.89%), while commissive and declarative acts were not identified. These findings suggest that the language used in Peter Drury’s goal commentaries extends beyond reporting match events, serving as a means of expressing emotion, evaluation, and audience engagement. This study contributes to the fields of pragmatics, sports discourse, and media linguistics by offering a focused analysis of illocutionary acts in the language of football goal commentaries.